Exposure to mixtures of mercury, cadmium, lead, and arsenic alters the disposition of single metals in tissues of Wistar rats. Issue 24 (17th December 2018) - Orr, Sarah E.; Barnes, Mary C.; George, Hannah S.; Joshee, Lucy; Jeon, Byunggwon; Scircle, Austin; Black, Oscar; Cizdziel, James V.; Smith, Betsy E.; Bridges, Christy C.
ABSTRACT: Humans throughout the world are exposed regularly to mixtures of environmental toxicants. Four of the most common heavy metal toxicants in the environment are mercury (Hg), cadmium (Cd), lead (Pb), and arsenic (As). Numerous studies have assessed the effects and disposition of individual metals in organ systems; however, humans are usually exposed to mixtures of toxicants or metals rather than to a single toxicant. Therefore, the purpose of the current study was to test the hypothesis that exposure to a mixture of toxic heavy metals alters the disposition of single metals in target organs. Wistar rats ( Rattus norvegicus ) were exposed to Hg, Cd, Pb, or As as a single metal or as a mixture of metals. Rats were injected intravenously for three days, following which kidneys, liver, brain, and blood were harvested. Samples were analyzed for content of Hg, Cd, Pb, and As via inductively coupled plasma mass spectrometry. In general, exposure to a mixture of metals reduced accumulation of single metals in target organs. Interestingly, exposure to mixtures of metals with Pb and/or As increased the concentration of these metals specifically in the liver. The findings from this study indicate that exposure to mixtures of toxic heavy metals may alter significantly the distribution and accumulation of these metals in target organs and tissues.